2001
DOI: 10.1063/1.1344218
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microwave power on the structural and emission properties of hydrogenated amorphous silicon carbide deposited by electron cyclotron resonance chemical vapor deposition

Abstract: Hydrogenated amorphous silicon carbide (a-Si 1Ϫx C x :H) films have been deposited using an electron cyclotron resonance chemical vapor deposition system. The effects of varying the microwave power from 100 to 1000 W on the deposition rate, optical band gap, film composition, and disorder were studied using various techniques such as Rutherford backscattering spectrometry, spectrophotometry, Fourier-transform infrared absorption, and Raman scattering. Samples deposited at 100 W are found to have a carbon fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 55 publications
3
13
0
Order By: Relevance
“…In a-C/H/Si films (Si/DLC), the I D /I G ratio is related to the size of the aromatic clusters in the films [16] and the PL effect can be interpreted with this cluster size too. The broadening of PL as we observed in our film may be attributed to the disorder broadening arising from the broadband tails [17]. The PL effect of these films can also be explained with the help of C-H n (s) and Si-H n bonding intensity as shown in Fig.…”
Section: Raman and Pl Analysismentioning
confidence: 80%
“…In a-C/H/Si films (Si/DLC), the I D /I G ratio is related to the size of the aromatic clusters in the films [16] and the PL effect can be interpreted with this cluster size too. The broadening of PL as we observed in our film may be attributed to the disorder broadening arising from the broadband tails [17]. The PL effect of these films can also be explained with the help of C-H n (s) and Si-H n bonding intensity as shown in Fig.…”
Section: Raman and Pl Analysismentioning
confidence: 80%
“…The broadening of PL, i.e. the increase of FWHM of the PL peaks of all the samples, may be attributed to the disorder broadening arising from the broadband tails [28]. It is shown in Fig.…”
Section: Photoluminescence Studymentioning
confidence: 97%
“…[1][2][3] In this study, we investigate a-Si 1Ϫx C x :H films grown with the electron cyclotron resonance chemical vapor deposition ͑ECR-CVD͒ technique, which has the unique characteristics of a high plasma density, high electron temperature, and controllable ion energy that can be independent of the degree of plasma ionization. 4,5 In our previous study on the effect of microwave power on ECR-CVD grown a-Si 1Ϫx C x :H, it was noted that the Si-C infrared absorption band at ϳ800 cm Ϫ1 can only be clearly seen for films deposited at high microwave powers beyond 800 W. 6 On the effect of hydrogen incorporation in a-Si 1Ϫx C x :H, previous reports have shown that stronger hydrogen dilution in the gas mixture will lead to films with lower defect densities and smaller Urbach energies, and result in improved optoelectronic properties, such as enhanced photoconductivity. 7,8 Based on these considerations, it is interesting to study a-Si 1Ϫx C x :H films with different carbon fractions ranging from xϭ0 (a-Si:H) to xϭ1 (a-C:H), deposited under a combination of high microwave power and strong hydrogen dilution.…”
Section: Introductionmentioning
confidence: 99%